Vitamin C and its Role in Pregnant Ewes: Subject Review - Asaad, Nahla Kamal; Omer, Esam Saeed; Ameen, Sameerah Hussein (American Journal of Biodiversity, 2025)
It is an important antioxidant vitamin that helps protect cells from damage and water-soluble vitamins. It is important for the production of collagen, which is considered the main protein in connective tissues. Pregnancy in ewes represents a sensitive physiological period characterized by increased metabolic activity accompanied by an increased production of free radicals (Reactive Oxygen Species – ROS). This leads to oxidative stress, which can negatively impact the health of both the mother and fetus. Therefore, vitamin C (ascorbic acid) It is effective and important in neutralizing free radicals. Although the liver of ruminants including sheep has the ability to synthesize vitamin C from glucose, scientific evidence suggests that this capacity may be insufficient during pregnancy, especially in the presence of external factors such as heat stress or malnutrition. Studies indicate that adding vitamin C may improve biomarkers of oxidative stress, such as decreased malondialdehyde concentrations and increased activity of antioxidant enzymes such as superoxide dismutase and glutathione peroxidase, which contributes to protecting tissues from oxidative damage. While field research has shown that the use of vitamin C supplements during pregnancy improves immune function in pregnant ewes by enhancing the response of lymphocytes and raising levels of IgG and IgM antibodies, which positively impacts the mother’s resistance to disease and the transfer of passive immunity to the offspring. From a reproductive perspective, supplementation reduced fetal absorption rates, improved lamb birth weight, and supported placental development, suggesting an indirect role of vitamin C in improving overall reproductive efficiency. Results vary depending on the dose used and the period of administration. It has been shown that doses between 1-3 grams per day during the second half of pregnancy are the most effective without any apparent side effects. These data highlight the value of considering vitamin C but also as a supportive nutrient, but also as an important component of reproductive nutrition programs for pregnant ewes, especially in intensive production systems or harsh environmental conditions. When using of vitamin C can improve productivity in ruminants.